Positive breastfeeding experiences and facilitators in mothers of preterm and low birth weight infants: a meta-ethnographic review - Flacking Renée; Silnes Tandberg Bente; Niela-Vilen Hannakaisa; Jónsdóttir Rakel B; Jonas Wibke; Ewald Uwe; Thomson Gill (United Kingdom, 2022)
Background: Most qualitative research on breastfeeding the preterm or low-birthweight (LBW) infant has focused on negative insights; there are no comprehensive insights into how, when and why mothers experience positive breastfeeding experiences. We aimed to address this knowledge gap by exploring what characterizes and facilitates a positive breastfeeding experience in mothers of preterm and/or LBW infants.
Methods: A systematic review using meta-ethnographic methods was conducted. Search strategies involved a comprehensive search strategy on six bibliographic databases, citation tracking and reference checking. The analysis involved a reciprocal level of translation and a line of argument synthesis.
Results: Searches identified 1774 hits and 17 articles from 14 studies were included, representing the views of 697 mothers. A positive breastfeeding experience was identified as being 'attuned'. Three themes and eight sub-themes were developed to describe what characterizes attuned breastfeeding. 'Trusting the body and what it can do', concerned how attuned breastfeeding was facilitated through understanding the bodily responses and capacity and feeling comfortable with holding the infant and to breastfeed. 'Being emotionally present - in the here and now' described the importance of feeling relaxed and reassured. 'Experiencing mutual positive responses', illuminated how attunement was related to feelings of mutuality - when the mother recognises the infant's cues, responds to these signals and receives a positive response from the infant. The key factors to facilitate attuned breastfeeding were opportunities for prolonged close physical contact with the infant, positive relationships with and support from staff and peers, and being facilitated to breastfeed when the infant showed feeding cues.
Conclusions: This study provides new insights into what characterizes a positive breastfeeding experience and how staff can facilitate and enable mothers to achieve attuned breastfeeding. Improvements in units' design, such as for rooming-in and having prolonged skin-to-skin contact, and care provided by knowledgeable, supportive and encouraging staff and peers, are crucial. The mother's physical and emotional states and the infant's behavioural responses and physiological signals should guide the process towards positive breastfeeding practices.